Rise of Agritech: A landscape of technology driven agricultural sector in India - Haritha K; Akriti Sharma; P Venkatesh; Asha Devi; P Anbukkani; Abhinandan Kumar (Agricultural Economics Research Review, 2024)
The rising demand for innovation in agriculture and the decreasing last-mile delivery to farmers have led to introduction of new technologies in the agriculture ecosystem. With advancements in and application of information technology in agriculture, agritech has been increasingly gaining attention. The present study has investigated the geographical and funding landscape of agritech companies in India. It has identified the technological and business models that are predominant in the Indian scenario. The study is based on the secondary data of 253 agritech companies in India (till 2022) collected from the CrunchBase database. The study has presented summary statistics, tabular and graphical representation, and content analysis for these business models. The results have revealed that the incorporation trend has increased in India over the past few years. The total funding has also shown an increasing trend over the years. Among states, Karnataka has emerged as the hotspot of agritech companies in India, followed by Maharashtra. With the help of Inductive content analysis of the textual data, the study has identified the supply chain technology and output market linkages, followed by the farm management and analytics as the most promising business models in the Indian context.